Avaliação da educação superior: ações de internacionalização e sua influência no conceito CAPES - Rocha, Denize Barreto (2024)
This paper investigates the role of internationalization actions in the Postgraduate Program in Social Psychology (PPGPS) at the Federal University of Paraíba (UFPB) and its repercussions on the evaluation carried out by the Coordination for the Improvement of Higher Education Personnel (CAPES) for the four-year period, 2017- 2020. The study highlights internationalization as a crucial vector for contemporary higher education, driven by the process of globalization and social, cultural and economic transformations that demand education with a global perspective. Internationalization is discussed as an integration of international, intercultural or global dimensions into the purposes, functions and provisions of higher education, indicating the evolution of cooperative and student mobility to a broader concept that encompasses international skills, global rankings, among other aspects. The general objective of this study was to evaluate the internationalization actions of the PPGPS, with the support of institutional policy, taking the CAPES quadrennial evaluation (2017- 2020) as a parameter. To achieve this objective, a qualitative and descriptive methodology was adopted, using documentary and observational procedures for data collection and analysis. This approach allowed for an in-depth understanding of the policies, practices and impacts of internationalization on the program in question. This research is justified by the need to understand how internationalization actions can influence indicators of quality and academic excellence, contributing to raising the program's concept in CAPES evaluation. The results obtained showed that the PPGPS has implemented several internationalization actions, which include the promotion of academic mobility, international scientific production, and collaboration in 01 global research networks. Such actions reflect alignment with CAPES guidelines and demonstrate an institutional commitment to internationalization. However, challenges were also identified, such as the need for greater institutionalization of these practices and strategies to increase the program's international visibility. The conclusion of the study highlights that the internationalization actions of the PPGPS contributed positively to its concept in the CAPES assessment, corroborating the initial hypothesis that internationalization constitutes a strategic dimension for improving quality and academic performance. The study also concludes that internationalization in higher education must be understood and practiced as a continuous process and integrated with institutional development policies, reinforcing the need for public and management policies that encourage internationalization as an essential part of academic excellence and social contribution of higher education institutions.